Vitamin D Deficiency in Children of School Age Bone Pathology - Elomonovna, Urakova Umida (European Journal of Life Safety and Stability (2660-9630), 2023)
Vitamin D deficiency, that is, rickets, is a disease that occurs only in young children with life-long complications. It is caused by a lack of vitamin D in the child's body. The body needs calcium and phosphorus elements for the development of the child, especially for bone growth and strength. Vitamin D controls the absorption of calcium and phosphorus from the intestine, their delivery to bones, muscles and other body tissues. This article provides information on the complications of vitamin D deficiency in children under school age.